PENDAFTARAN PERALIHAN HAK ATAS TANAH SEBAGAI HARTA BERSAMA (Studi Kasus Jual Beli Tanpa Izin Suami, Isteri Dan Anak) - Angraini, Yuni; Silviana, Ana (Legal Standing : Jurnal Ilmu Hukum, 2023)
Registration of the Transfer of Land Rights can be done if a deed of transfer has been drawn up from the PPAT. Registration of the transfer of land rights often results in problems in buying and selling joint property land rights because there is no consent from the husband/wife and their adult children. This research wants to examine, first, what are the legal consequences of transferring rights to land in a joint property without the permission of the husband/wife and their adult children.; second, what is the Head of the Bandar Lampung City Land Office's attitude towards transferring rights to joint property land without the permission of the husband/wife and adult children? This research was conducted using a normative approach and an empirical approach. A normative process is carried out by collecting and studying applicable legal regulations closely related to research problems, including laws and regulations, official documents, and other sources related to the issues explored. An empirical approach is taken by looking at the reality of the registration process at the Land Office. The results of this study indicate that the legal consequences of transferring land rights to joint property without the consent of the husband/wife and adult children can be cancelled because the terms of the agreement still need to be fulfilled. Therefore, the Head of the Land Office of the City of Bandar Lampung refuses to register the transfer of rights if, in the process of buying and selling land rights for joint property, it is known that there is no consent from the husband/wife and adult children.